Multilingual global cities : Singapore, Hong Kong, Dubai - Siemund, Peter, 1965-; Leimgruber, Jakob R. E. (Jakob Robert Eugen), 1980- (Abingdon, Oxon ; New York, NY : Routledge, 2021)
"This volume sets out to investigate the linguistic ecologies of Singapore, Hong Kong and Dubai, with chapters that combine empirical and theoretical approaches to the sociolinguistics of multilingualism. One important feature of this publication is that that the five parts of the collection deal with such key issues as the historical dimension, language policies and language planning, contemporary societal multilingualism, multilingual language acquisition, and the localized Englishes of global cities. The first four sections of the volume provide a multi-levelled and finely-detailed description of multilingual diversity of three global cities, while the final section discusses postcolonial Englishes in the context of multilingual language acquisition and language contact"--
OCLC-licensed vendor bibliographic record.
Keywords: Cities and towns -- Sociological aspects -- Case studies; Multilingualism -- Case studies; English language -- Variation -- Case studies; Language and culture -- Case studies; LANGUAGE ARTS & DISCIPLINES / General